Has2 Regulates the Development of Ovalbumin-Induced Airway Remodeling and Steroid Insensitivity in Mice - Sherpa, Mingma Thsering; Kiwamoto, Takumi; Matsuyama, Masashi; Tsunoda, Yoshiya; Yazaki, Kai; Yoshida, Kazufumi; Nakajima, Masayuki; Matsuno, Yosuke; Morishima, Yuko; Ishii, Yukio; Hizawa, Nobuyuki (Frontiers in Immunology, 2022)
HAS2 is a member of the gene family encoding the hyaluronan synthase 2, which can generate high-molecular-weight hyaluronan (HMW-HA). Our previous study identified HAS2 as a candidate gene for increased susceptibility to adult asthma. However, whether HAS2 dysfunction affects airway remodeling and steroid insensitivity is still limited. Therefore, this study aimed to clarify the Has2 dysfunction, triggering severe airway remodeling and steroid insensitivity in a murine model of asthma. OVA stimulation was used to induce eosinophilic airway inflammation and remodeling in Has2 heterozygous-deficient (Has2+/−) mice and their wild-type littermates. After chronic OVA stimulation, Has2+/− (Has2+/−-OVA) mice showed significantly decreased Has2 mRNA expression levels, HMW-HA, HA-binding protein, and TGF-β. Has2+/−-OVA mice demonstrated increased eosinophilic airway inflammation, goblet cell hyperplasia, and high IL-17 levels. RNA sequencing demonstrated downregulation of EIF2 signaling pathways, TGF-β signaling pathways, and heat shock proteins with Th17 bias in Has2+/−-OVA mice. Combined treatment with anti-IL-17 antibody and dexamethasone reduces steroid insensitivity in Has2+/−-OVA mice. Has2 attenuation worsens eosinophilic airway inflammation, airway remodeling, and steroid insensitivity. These data highlight that HAS2 and HMW-HA are important for controlling intractable eosinophilic airway inflammation and remodeling and could potentially be exploited for their therapeutic benefits in patients with asthma.